A Causal Comparative Study Of Family Demography, Psychological Traits And Academic Achievement Of Nigerian Adolescent Girls Involved In Street Hawking - Ago, Habu Abdulrahman (2018)
In Nigeria, many school going adolescent girls have to work as street hawkers. It is a serious and challenging educational issue for many parties. This research aimed to examine the family demography, psychological traits and academic achievement of adolescent girls involved in street hawking at Yobe state, Nigeria using a Causal Comparative Study. The discussion in the study is underpins by the theoretical framework of Ecological System Theory, Theory of Reason and Action, Self-Efficacy Theory and Risk-Resilience Theory. A total of 394 respondents were involved in the quantitative study comprising of both adolescent girls involved and uninvolved in street hawking.